Damages of Neuromuscular System After Mechanical-Induced Limb Ischemia (Experimental Study) - Pidlisetskyi , A.T. (TERRA ORTHOPAEDICA, 2021)
Relevance. Traumatic and ischemic injury of the limbs is accompanied by damage of the skeletal muscles and peripheral nerves of the limbs. The dynamics and consequences of ischemic lesions remain poorly understood and need to be corrected. Objective: using quantitative morphological and sonographic methods, to study the dynamics of skeletal muscle damage of the limb after traumatically induced ischemia with and without the injection of platelet-rich plasma, bone marrow aspirate, and adipose tissue fraction. Materials and Methods. In 3 experiments, rabbits were modeled with 6-hour limb ischemia by applying an elastic tourniquet. After compartment syndrome detection, based on the assessment of subfascial pressure, cell suspensions were injected into the leg muscles. Sonographic and histological examination of the muscles was performed on days 5, 15, and 30. The results of sonography and morphometry were evaluated by statistical methods. Results. The developed model of ischemia consists of 6-hour immobilization of the limb, on тwhich medical elastic tourniquets were imposing. The action of the tourniquets causes high subfascial pressure and necrosis of the superficial muscle groups of the lower third of the thigh and lower leg. According to sonography, the δ-entropy of damaged tissues on day 5 is reduced relative to the intact limb, as in the case of administration of bone marrow aspirate cells. On days 15 and 30, sonography showed no difference between the comparison groups. The dynamics of morphological features of limb tissue damage consist of necrosis of superficial muscle groups, atrophy in the middle layers, and almost intact deep muscle groups. Necrosis was replaced by scar tissue, the density of which increases 11-14 times, and does not differ in the period 5-30 days. The administration of platelet plasma, bone marrow aspirate, and adipose tissue fraction did not change the dynamics of fibrotic changes in ischemic damaged muscles. Muscle atrophy is accompanied by activation of endogenous repair of single muscle fibers, which tended to intensify after injection of bone marrow aspirate. The sciatic nerve of the injured limb was not structurally damaged according to the deep topography, while the nerves of the tibia develop degenerative changes from the 15th day.